The Cultural Dimension in Geography - Afolabi Ojo, G. J. (Obafemi Awolowo University Press, 2012)
From the time I first became actively engaged in the geographer's craft, I have often wondered at how varied are the dimensions in the discipline. I am using the word dimensions to mean perspectives or points of view. Outside the opinions held by professionals, there are certain views expressed by the layman who probably had a smattering of what is called geography in the secondary schools. The layman might have dropped the subject in class three or four shortly before starting his school certificate simply because he was unable to cope with drawing maps or interpreting contours or because he was lured away by the combination of science subjects. Although he might have become a distinguished physicist or lawyer afterwards, the questions he asks of a geographer are illustrative of what may be described, in loose terms, as the layman's perspective on the subject. Samples of such questions are: What is the altitude of Ife? Why is the harmattan lingering on till March this year? How many miles, by road, is it from here to Kaura Namoda if I choose to go by the way of lIorin, Zungeru and Funtua? Both here and elsewhere, as George Kirnble has put it, "many people still think of the geographer as a dealer in terrestrial bric-a-brac, whose social function is to provide other people with answers to quiz questions".